(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2018)
This article has no abstract. The first 100 words appear below: A 10 month old baby girl, hailing from the Cumilla (a city in the Chattogram Division), Bangladesh was brought to the Department of Hematology, Armed Forces Institute of Pathology, Dhaka Cantonment, Dhaka, Bangladesh with the complaints of fever and cough for the last seven days. With these complaints, the parents initially took the child to a local child specialist. The child specialist gave initial supportive medications and advised to investigate the complete blood count, urine routine and microscopic examination and Widal test. After 2 days, the parents again took the baby to the child specialist for reviewing the child and to show the investigations result.